Modulation of Neuro-Inflammatory Signals in Microglia by Plasma Prekallikrein and Neuronal Cell Debris - Jaffa, Aneese A.; Jaffa, Miran A.; Moussa, Mayssam; Ahmed, Ibrahim A.; Karam, Mia; Aldeen, Kawthar Sharaf; Al Sayegh, Rola; El-Achkar, Ghewa A.; Nasrallah, Leila; Yehya, Yara; Habib, Aida; Ziyadeh, Fuad N.; et al. (Frontiers in Pharmacology, 2021)
Microglia, the resident phagocytes of the central nervous system and one of the key modulators of the innate immune system, have been shown to play a major role in brain insults. Upon activation in response to neuroinflammation, microglia promote the release of inflammatory mediators as well as promote phagocytosis. Plasma prekallikrein (PKall) has been recently implicated as a mediator of neuroinflammation; nevertheless, its role in mediating microglial activation has not been investigated yet. In the current study, we evaluate the mechanisms through which PKall contributes to microglial activation and release of inflammatory cytokines assessing PKall-related receptors and their dynamics. Murine N9-microglial cells were exposed to PKall (2.5 ng/ml), lipopolysaccharide (100ng/ml), bradykinin (BK, 0.1 μM), and neuronal cell debris (16.5 μg protein/ml). Gene expression of bradykinin 2 receptor (B2KR), protease-activated receptor 2 (PAR-2), along with cytokines and fibrotic mediators were studied. Bioinformatic analysis was conducted to correlate altered protein changes with microglial activation. To assess receptor dynamics, HOE-140 (1 μM) and GB-83 (2 μM) were used to antagonize the B2KR and PAR-2 receptors, respectively. Also, the role of autophagy in modulating microglial response was evaluated. Data from our work indicate that PKall, LPS, BK, and neuronal cell debris resulted in the activation of microglia and enhanced expression/secretion of inflammatory mediators. Elevated increase in inflammatory mediators was attenuated in the presence of HOE-140 and GB-83, implicating the engagement of these receptors in the activation process coupled with an increase in the expression of B2KR and PAR-2. Finally, the inhibition of autophagy significantly enhanced the release of the cytokine IL-6 which were validated via bioinformatics analysis demonstrating the role of PKall in systematic and brain inflammatory processes. Taken together, we demonstrated that PKall can modulate microglial activation via the engagement of PAR-2 and B2KR where PKall acts as a neuromodulator of inflammatory processes.